2015
DOI: 10.3923/ajava.2015.295.310
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Feeding Fish the Dried-Treated Sewage on Physiological Responses and Histological Structure of the Liver

Abstract: Fish are one of the most extensively distributed organisms in the aquatic environment. A field study was conducted for 102 days at feeding period. A 100 fish/net-Hapa (Nile tilapia, silver carp, common carp and African catfish) were stocked at a rate of 1: 1: 1: 1 using a polyculture system. Two experimental net-Hapa/treatment were used, one treatment as a control fish fed a commercial diet and the second one fish were fed a Dried Sewage Sludge (DSS), product of treating sanitary and agricultural drainage of A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…The reason for higher lactate values may be due to their increased feeding habits and related more physiological activities. Active swimmers have high glucose and lactate levels as compared to less active sluggish forms [5,7,12,20,27,28]. Another reason for high serum lactate levels may be due to large amounts of glycogen present in the liver of the experimental fish is converted in to lactate [7,15,29].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The reason for higher lactate values may be due to their increased feeding habits and related more physiological activities. Active swimmers have high glucose and lactate levels as compared to less active sluggish forms [5,7,12,20,27,28]. Another reason for high serum lactate levels may be due to large amounts of glycogen present in the liver of the experimental fish is converted in to lactate [7,15,29].…”
Section: Resultsmentioning
confidence: 99%
“…Fishes and their biochemical parameters can be considered as bio-indicators or bio-monitors of aquatic system for assessing the quality of water and also the survival and growth rates of fishes grown in such environments [8][9][10][11][12][13][14][15]. Bio-chemical and pathological changes of fishes exposed to varying degrees and types of environmental pollution or stress have been measured by several investigators since last many years [9,[16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…Sewage sludge feeding did not negatively affect the blood picture in general. Yet, Abdelhamid et al [16] revealed that regardless of fish species, only RBCs, WBC and PLT reflected significant differences between both dietary treatments (dried sewage sludge versus control) with higher values for sewage sludge fed fish. However, catfish gave significantly higher values for most of the hematological parameters referring to best tolerance among the studied fish species.…”
Section: Haematological Parametersmentioning
confidence: 98%
“…It includes the erythrocytes or red blood cells (RBCs) count, leucocytes or white blood cells (WBCs) count, platelets counts, and haemoglobin (Hgb or Hb) concentration. However, there is no standard ranges for fish haematological parameters; since, not only fish species is responsible for haematological variations [14], but also it is affected by stress factors [15], dietary supplements [16], nutritional treatments [14], immunstimulators [17], culture systems [18], and pollution [14].…”
Section: Haematological Parametersmentioning
confidence: 99%
See 1 more Smart Citation